Mikroenkapsulasi Karbamazepin dengan Polimer HPMC Menggunakan Metoda Emulsifikasi Penguapan Pelarut - Rina Wahyuni; Auzal Halim; Yustina Susi Irawati (STIFARM Padang, 2015)
Microencapsulation of Carbamazepine using HPMC as a polymer by emulsification solvent evaporation method had been studied. Microcapsules had been made into 3 formulation with 3 ratio variation between Carbamazepine and HPMC, 1:1; 1:1.5; 1:2. Microcapsules were evaluated by SEM, DTA, FT-IR, particle sized distribution, drug content and dissolution profile. The evaluation result showed that HPMC as a polymer of sustained release was influence characteristic microcapsules of Carbamazepine. Microcapsules were white to slightly yellow and almost perfectly spherical. Disolution profiles of microcapsules showed that the formula containing the greatest amount of HPMC gave the slower release of Carbamazepine. Resistance release of biggest drug shown by formula 3 giving disolution during 6 hour counted 24.5296 %. Dissolution kinetics of microcapsules allowed Higuchi equation, where the realese of Carbamazepine from microcapsules were controlled by diffution process.